2022
DOI: 10.1002/smll.202204693
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Flow Microfluidic Production of Arbitrarily Long Tubular Liquid Crystal Elastomer Peristaltic Pump Actuators

Abstract: While liquid crystal elastomers (LCEs) are ideal materials for soft‐robotic actuators, filling the role of muscle and shape‐defining material simultaneously, it is non‐trivial to give them ground state shapes beyond simple sheets or fibers. Here tubular LCE actuators scalable to arbitrary length are produced using a continuous three‐phase coaxial flow microfluidic process. By pumping an oligomeric precursor solution between inner and outer aqueous phases in a cylindrically symmetric nested capillary set‐up, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Even when starting with polymeric solutes, the evaporation of solvent will lead to phase separation at some point. During our microfluidic fabrication of nematic LCE tubes from LCO solution (Najiya et al, 2022), we found clear evidence by electron microscopy of phase separation influencing the final LCE structure. We believe that its occurrence in the presence of shear flow has profound consequences on the final chain organisation and the mode of actuation of the resulting LCE tube.…”
Section: Processing Challengesmentioning
confidence: 86%
See 1 more Smart Citation
“…Even when starting with polymeric solutes, the evaporation of solvent will lead to phase separation at some point. During our microfluidic fabrication of nematic LCE tubes from LCO solution (Najiya et al, 2022), we found clear evidence by electron microscopy of phase separation influencing the final LCE structure. We believe that its occurrence in the presence of shear flow has profound consequences on the final chain organisation and the mode of actuation of the resulting LCE tube.…”
Section: Processing Challengesmentioning
confidence: 86%
“…Very recently, we succeeded in making the first arbitrarily long LCE tubes in a microfluidic setup, pumping an isotropic LCO solution between two aqueous polymer solutions used as inner and outer phases, and adding strategically selected surfactants to all phases to achieve such low interfacial tension that the break-up of the tube due to the Rayleigh-Plateau instability is prevented (Najiya et al, 2022). Upon in situ UV-irradiation-triggered photocrosslinking, the isotropic tubular precursor flow is converted into a nematic LCE tube which can drive peristaltic pumping of a contained liquid when moving a hot point along the tube.…”
Section: (C) Three Different Sections Cut From Negative-order Paramet...mentioning
confidence: 99%
“…In this context, Lagerwall et al report the continuous flow microfluidic production of liquid crystal elastomer-based actuators. [15] Artificial cells was a subject of several reports addressing different challenges and opportunities. For instance, Han et al develop artificial cells that contain cyanobacteria, to harvest energy from light and perform the synthesis of glucose using CO 2 as a carbon source.…”
mentioning
confidence: 99%